(untitled) (Research, Society and Development, 2021)
The objective was to describe the intensive care of cardiovascular nursing to neonates with congenital heart disease. The adopted design was an integrative review, whose search period occurred between the months of August-November/2020 for articles indexed in the last ten years in the databases. 21 articles were selected / included in the investigation and the main critical nursing care for newborns with congenital heart diseases was listed. Such care encompassed interdisciplinary action in the processes of disease prevention, health promotion, early diagnosis in a clinical, laboratory and imaging way, as well as in the processes of clinical, pharmacological or surgical treatment in favor of rehabilitation, cure or the establishment of a favorable prognosis for the child. It is concluded that the role of the nurse and his team in this approach in the intensive context is systematized within the nursing process and must occur in an interdisciplinary way, integrated with the other professionals, aiming at a safe, quality, effective and humanized care.